Investigating the prevalence of abnormal coagulation factors in people living with Human Immunodeficiency Virus on Antiretroviral Therapy: A retrospective cohort. - Sidandala, Sibusiso; Thembane, Nokukhanya; Jaya, Ziningi (Student's Journal of Health Research Africa, 2025)
Background The prevalence of coagulation abnormalities in people living with human immunodeficiency virus (PLHIV) has reduced due to highly active antiretroviral therapy (HAART). However, HAART for HIV may harm the liver, resulting in the disruption of coagulation factor production in the liver. Therefore, it is imperative to understand the extent of coagulation abnormalities within this population to inform healthcare management and intervention strategies. This research aimed to investigate the prevalence of abnormal coagulation factors in PLHIV. Methodology This study analysed retrospective laboratory data from HIV-positive individuals on HAART in eThekwini District Municipality, collected between January 2021 and January 2022 at a tertiary hospital laboratory in Durban. The investigation focused on coagulation factor profiles in this patient population. All results were obtained from the National Health Laboratory Services (NHLS) Academic Affairs and Research Management System (AARMS). Excel was used to conduct descriptive statistics, and GraphPad Prism was utilised for comparative analyses (Spearman correlations) to evaluate factor abnormalities. Results Fifty-seven percent of the results were from females, and a significant portion of the results were for individuals aged between 35 to 54 years. A total of 70% of the prothrombin time (PT) results and 16.5 of % activated partial thromboplastin time (aPTT) results were abnormally above the normal range. Women were disproportionately affected by this abnormality at 55,5%. There was a poor and significant inverse correlation between CD4 cell count and PT and INR. Conclusion The study findings highlighted notable coagulation abnormalities among HIV infected patients on HAART, with a particularly higher prevalence among females and individuals aged between 35 – 54 years. Recommendation Regular monitoring of coagulation factors is imperative for early identification of individuals at risk of developing related abnormalities and thus informs the development of effective healthcare interventions.